Essential Blogging - Doctorow, Cory (O'Reilly, 2011)
With weblogs-or "blogs"-exploding all over the Web, the only thing lacking for power users and developers is detailed advice on how choose, install, and run blogging software. Written by leading bloggers, Essential Blogging includes practical advice and insider tips on the features, requirements, and limitations of applications such as Blogger, Radio Userland, Movable Type, and Blosxom. This book will get you up and blogging in no time.